Deep Transient Slow Slip Detected by Survey GPS in the Region of Atacama, Chile. Issue 22 (26th November 2018) - Klein, E.; Duputel, Z.; Zigone, D.; Vigny, C.; Boy, J.‐P.; Doubre, C.; Meneses, G.
Abstract: We detected a long‐term transient deformation signal between 2014 and 2016 in the Atacama region (Chile) using survey Global Positioning System (GPS) observations. Over an ∼150 km along‐strike region, survey GPS measurements in 2014 and 2016 deviate significantly from the interseismic trend estimated using previous observations. This deviation from steady state deformation is spatially coherent and reveals a horizontal westward diverging motion of several centimeters, along with a significant uplift. It is confirmed by continuous measurements of recently installed GPS stations. We discard instrumental, hydrological, oceanic, or atmospheric loading effects and show that the transient is likely due to deep slow slip in the transition zone of the subduction interface (∼40‐ to 60‐km depth). In addition, daily observations recorded by a continuous GPS station operating between 2002 and 2015 highlight similar transient signals in 2005 and 2009, suggesting a recurrent pattern. Plain Language Summary: The dense development of Global Positioning System (GPS) networks along plate boundaries worldwide has allowed us to observe different fault behaviors: long‐term deformation over decades to centuries or the motion generated by major earthquakes. We also observe slow slip events, occurring over weeks to months, creating significant motion without generating seismic waves. These events are observed on most subduction zones on Earth, repeating regularly. Usually occuring at depth larger than 40 km, they are often associated with long‐lasting low amplitudes seismic vibrations. Although the Chilean subduction zone is one of the most active on Earth, no such slow event has yet been observed. Using survey GPS observations since 2010 in the region of Atacama (Central North Chile), completed by continuous observations, we have detected a transient signal between 2014 and 2016. After investigating all possible sources, we demonstrate that a deep slow slip event is the most likely origin. Despite a quite sparse seismic network in this region, the seismic observations show an unusual long‐lasting low amplitudes seismic activity. Going further, the observations recorded by a GPS station operational since 2002 shows similar signals in 2009 and 2005, highlighting a recurrent pattern of slow slip events in the Atacama region. Key Points: We detected a transient signal that occurred between 2014 and 2016 in Central North Chile using sGPS data We rejected any nontectonic source such as instrumental or hydrological processes These observations confirmed by cGPS are explained by slow slip events in the transition zone of the megathrust